"ACHIL", A TACKLE FOR SARDINES - Lazarus, S (Indian Journal of Fisheries, 2011)
Sardines are normally caught by gill nets and seine nets. Apart fromthese, several indigenous types of gears have been developed by fishermento suit local conditions, which, though primitive and crude in appearance,are efficient in their own ways. 'Achil', a type of hand line, is onesuch gear developed and used to capture the lesser sardines and the rainbowsardines along the south-west coast of India between Varkkala and CapeComorin. Since good results are obtained for the small cost (Rs. 3.50 per unit)and the little effort (one man-day only) the gear is used extensively by fishermensince 1972 in this stretch of the coas